Gender : Stress Levels On Performance In Modern Industry - Soelton, Mochamad; Nugrahati, Tati; Setiawan, Margono; Rohman, Fatchur; Pratama, Aditya (Archives of Business Research, 2019)
This research aims to understand the influence of gender and working stress on working performance. There are three independent variables and one dependent variable, namely gender influence, working stress and working environment as the independent variables and working performance as dependent variable. This study object is the employees in Jakarta. The research is conducted towards 161 respondents using quantitative descriptive approach method and slovin method. Data analysis is conducted by using double linier regression and is processed by using SPSS program Version 23. The result of the study shows that the gender and working environment have a positive and significant influence towards employees performance, and working stress has a negative and significant influence towards employees performance.